2020
DOI: 10.1186/s43093-020-00012-1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental technology and a multiple approach of competitiveness

Abstract: This paper investigates the relationships between environmental technology and competitiveness focusing on 224 industrial corporations. To date, there is still a debate regarding the benefits of being green. Previous literature has investigated this relationship mostly in developed countries. Additionally, the majority of these studies do not disaggregate the environmental practices and competitiveness. Less attention has been given to the environmental issues in developing countries. This study aims to fill t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…These four dimensions have been progressively studied with empirical evidence. Noteworthy studies in the context include: Salem et al (2020), which looks at the role of environmental technologies in improving organisations' competitiveness, Ceptureanu et al (2020) and Thomas et al (2021), suggesting that eco-organisational innovation updates an organisation's management processes through new eco-methods to improve business performance by supporting necessary changes in business practices, Pecorari and Lima (2020) look at the role of eco-innovation considering the role of new products essentially and in Dahan and Yusof the role of process eco-innovation is essentially explored. Lastly, Kasztelan et al (2020) look at the importance of innovation systems as a strategy for green growth.…”
Section: Eco-innovationmentioning
confidence: 99%
“…These four dimensions have been progressively studied with empirical evidence. Noteworthy studies in the context include: Salem et al (2020), which looks at the role of environmental technologies in improving organisations' competitiveness, Ceptureanu et al (2020) and Thomas et al (2021), suggesting that eco-organisational innovation updates an organisation's management processes through new eco-methods to improve business performance by supporting necessary changes in business practices, Pecorari and Lima (2020) look at the role of eco-innovation considering the role of new products essentially and in Dahan and Yusof the role of process eco-innovation is essentially explored. Lastly, Kasztelan et al (2020) look at the importance of innovation systems as a strategy for green growth.…”
Section: Eco-innovationmentioning
confidence: 99%
“…When measuring AOCs, several studies in the literature used supervisor or colleague measures rather than self-reported measures. However, this study used the self-reported measure in light of previous studies [65] suggesting that individuals have a greater understanding of their AOCs than their supervisors or workmates. Participation was anonymous and voluntary, and to eliminate the risk of common method bias there were no right or wrong responses [66].…”
Section: Sample and Proceduresmentioning
confidence: 99%